Improving the inventory management system and retail operations of an importation company - Sison, Gabriel R. (Animo Repository, 2018)
This action research paper describes the challenges and opportunities of inventory management for an importation company in the Fast-Moving-Consumer-Goods Industry. Inventory Management is defined as the acquisition, storage and utilization of inventory to ensure sufficient stock for contingencies, optimize profitability and reduce wastage. The objectives of this research paper are to improve the company’s inventory management system and develop the capabilities of its employees to be proficient users of inventory management tools. Forecasting and capacity planning were one of the tools applied to address issues in the company’s inventory management. Kurt Lewin’s Change Management Model was used to design and manage change for stakeholders involved in the company’s supply chain and sales. Through a collaborative action research, the issues and drivers of inventory management were identified and addressed to establish a stable product supply across the company’s retail clients. The results of this research highlight the (1) Importance of communication and flow of information between key personnel in procurement and sales, (2) Impact of accurate inventory and sales information, (3) Capacity building of employees involved in inventory management and (4) The effect of inventory management to a company’s profitability. This research recommends improvements and company focus on primary drivers of a successful inventory management. According to Chan, et al., these are (1) Documentation, (2) Planning, (3) Skills and knowledge of employees and (4) Funds. Lastly, this research also recommends proper coordination and simultaneous development in purchasing and last-mile delivery to improve an organization’s inventory management.